Genetic parameters for egg production traits in KU KU-Phuphan black bone chicken population - Sukprasert, C.; Plaengkaew, S.; Khumpeerawat, P.; Lokaewmanee, K.; Abul Bashar, Md.; Deedar Parvez, A.K.M.; Suwanlee, S. (Diponegoro University, 2026)
Genetic parameters for egg production traits in the KU-Phuphan black bone chicken, a native Thai breed, were analyzed to estimate heritability, investigate genetic correlations, and provide essential genetic data for developing effective breeding strategies to improve egg production performance. The study focused on traits age at first egg (AFE) and cumulative egg production at 180, 270, 300, and 365 days. Data were collected from 541 hens across three generations raised in an open-house system. Ge-netic parameters, including heritability and genetic correlations, were estimated using the AIREMLF90 software with the average information restricted maximum likelihood method. The results revealed moderate heritability for AFE (0.41) and higher heritability estimates for cumulative egg production traits (0.30–0.50). Genetic correlations among egg production traits were high (0.93–0.99), indicating that these traits were influenced by similar genetic factors. However, the genetic correlations between AFE and egg production traits were low (0.18 to -0.02), suggesting that these traits were influenced by different genetic factors. In conclusion, the potential was highlighted for genetic selection to improve egg production traits in this breed. Therefore, in designing breeding programs, breeders should consid-er the high heritability of egg production traits and the low genetic correlations between AFE and egg production.